El outsourcing y la reducción de riesgos en revisoría fiscal para las Mipymes del siglo XXI en Colombia - Orjuela Barón, María Angélica (Universidad Antonio Nariño, 2021)
Today, both private and public organizations are entering the innovation registry through outsourcing. Especially in matters of tax audit. Since in the financial control mechanisms there are unprecedented alternatives for outsourcing accounting and tax services. The main objective of this strategy is to provide a quality service, oriented to the level of trust in the financial statements and under a culture of tax transparency. Outsourcing in this case allows micro, small and medium-sized companies to concentrate, in the best of cases, on the task of their social and economic purpose, while the provider of an accounting service monitors the proper functioning of their financial health.